Lithospheric Thermal Structure in Jinggangshan City: Implications for High Geothermal Background - Liao, Yuzhong; Liu, Yanguang; Liu, Feng; Wei, Shuaichao; Duan, Hexiao (Frontiers in Earth Science, 2022)
Jinggangshan City, which is located in the southwestern part of Jiangxi Province, is rich in hot springs. However, lack of geothermal studies has limited the exploration and utilization of the geothermal resources in this city. This study estimated the terrestrial heat flow in Jinggangshan City through well logging and analyses of rock thermal conductivity and heat production. Based on this and the surrounding geoscience transect and the Crust 1.0 model, this study constructed a one-dimensional lithospheric thermal structure by solving the steady-state heat conduction equation. Furthermore, the deep temperature distribution in Jinggangshan City was obtained to better understand the geodynamic condition of the geothermal resources in this city. The results show that the heat flow in this city is around 83.52 mW/m2, indicating the high heat background for the formation of geothermal resources. According to the lithospheric thermal structure of Jinggangshan City, the mantle contributes more to the terrestrial heat flow (qm/qc > 1) than the crust. The temperature of the Mohorovicic discontinuity (the Moho) is 671.7°C, which is consistent with that below the Tanlu deep fault (620–690°C). Moreover, the calculated depth of the Curie surface (585°C) is 27 km, which is consistent with the Curie isotherm depth estimated from aeromagnetic data. This consistency verifies the validity of the lithospheric thermal structure of Jinggangshan City constructed in this study. In summary, the high heat background plays an important role in the formation of geothermal resources in Jinggangshan City.